Transformation of isochorismate synthase in fungal system - Lim, Pei Wen (Universiti Malaysia Sarawak, UNIMAS, 2013)
Agrobacterium-mediated transformation is a powerful tool that allows the introduction of particular genetic changes in an organism. Transformation of fungi, Aspergillus niger is necessary to fulfill the increasing global industrial demand. Isochorismate synthase gene from Morinda citrifolia is important in the involvement of salicylic acid which plays a role in plant immunological system. In this study, the isolated plasmids pGSA1131/ICS were successfully transformed into Agrobacterium tumefaciens cells. A. tumefaciens carrying pGSA1131/ICS containing bacterial BAR-resistant gene have been used in A. niger transformation. Different concentration of growth media containing different concentration of selective agent, Basta, were used in the transformation to obtain a maximum yield of transformants. The growth of mycelia on top agar of PDA plates containing reduced concentration of Basta at 10 mg/L. The extracted fungal DNA was examined via PCR. A successful transformation of A. niger was achieved.